ILLUMINATION OF UNIVERSAL HUMAN VALUES IN MEDIA TEXT - Rahmonova Nuriya (American Journals Publishing, 2023)
In this article, information was given about the state and characteristics of media text in the language teaching system aimed at highlighting universal human values and developing intercultural communicative competence of students. The author expresses the specific features of the media text as a media component. The article reveals the classification of mass media texts, expresses the selection criteria for language teaching purposes.
Keywords: mediatext, intercultural approach to teaching, intercultural communicative competence, selection of mediatexts, didactical criteria of mediatexts, classification of mediatexts.